What health management topic frequently appeared in the New England Medical Journal (NEMJ) ? : a systemic review - A.L Khalib,; R Nirmalini, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Introduction : It is no doubt that the success of any health organization depends so closely on its managerial functions. To achieve this, the leader or manager as the core strategist of its organization must in all time be updated with the latest evidence-based information so that he or she can be easily operationalized his or her management function in more effective and sustainable manners. It depends largely on scientific literatures that published relevant articles within this scope. Unfortunately, management topics related to health care system is scattered published and this has indirectly affect manager to access the latest scientific documents. Methods : We examined the practice of well known international journal in health care namely New England Medical Journal (NEMJ) on its role in propagating latest health management topics to its prospective clients. Results : The result showed that a total of 31% health management topics were published throughout 2007 out of 1140 articles appeared. Of these, about 33% were confined to general health administration. The remaining articles were related to healthcare delivery practices (24%), medical ethics and legal matters (17% each), and manpower issues and training (9%). Conclusion : Focus on managerial related articles relatively low as compared to clinical and other evidence-based medicine that clearly dominated health management issues.